Albrecht Dürer And The 16th Century Melancholy - Rodrigues, Marcel Henrique (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
Little has been discussed in academia about the close relationship between the Renaissance of the 16th century and melancholy humor, and esoteric elements arising mainly from Florentine Neoplatonism. The link between melancholy and esotericism becomes very clear when we analyze the gravure “Melencolia I” by Albrecht Dürer (1471-1528), composed of a significant number of symbols that refer to an esoteric religious culture that then emerged. Renaissance melancholy gained several nuances. On the one hand, it was considered a sin, a despicable mood characteristic of witches; on the other hand, a deep sense of inspiration typical of men of “genius”. This ambivalence also occurred in the firmament, as the melancholic people were guided by the dark planet Saturn, according to astrological belief. We also have the cultural scenario of the 16th century, especially in Dürer's Germany, which contributed to strengthening the melancholy issues.